A MIMO LMS adaptive equalization approach in simulated radar emission - Junita, Mohd Nordin; Anuar, Mat Safar; Azremi, Abdullah Al Hadi; Norshaida, Ahmad; Shariffah Zarihan, Syed Zaharim Helmi; Bukhairi, M.N (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to pulisher's homepage at http://ieeexplore.ieee.org